Peran Ganda Perempuan Pedesaan dalam Rumah Tangga Petani Berperspektif Gender - Vi'in Ayu Pertiwi; Alia Fibrianingtyas; Risma Maulinda (Politeknik Pembangunan Pertanian Malang, 2024)
Employment in the agricultural industry in rural regions predominantly constitutes the primary occupation for men, while women provide auxiliary support to men. Ultimately, women fulfil a dual role; on one side, they serve as domestic workers who do not directly produce results or revenue, yet they provide essential help to others in securing employment and capitalising on available job prospects. Conversely, in alignment with societal advancements, women also serve as public workers who yield results directly or without remuneration, such as family labourers in agriculture. This study seeks to examine the dual function of women in both domestic and public spheres of labour. This study employs a quantitative descriptive methodology. The research was carried out at Morang Village, Madiun Regency, East Java. The study's findings indicate that women's dual role in rural agriculture is prominently evident through their responsibilities in childcare, managing children's education, cooking, and household cleaning, while simultaneously bearing the additional burden of external employment for financial sustenance, such as selling and factory work. Women in the community are also required to assist males in agricultural tasks, including land preparation, planting, weeding, pest and disease management, and harvesting, with the exception of nursery and marketing activities.